Synergistic activity between conventional antifungals and chalcone-derived compound against dermatophyte fungi and Candida spp. - Maschio-Lima, Taiza [UNESP]; Lemes, Thiago Henrique [UNESP]; Marques, Mariela Domiciano Ribeiro; Siqueira, João Paulo Zen; de Almeida, Bianca Gottardo; Caruso, Glaucia Rigotto; Von Zeska Kress, Marcia Regina; de Tarso da Costa, Paulo [UNESP]; Regasini, Luis Octávio [UNESP]; de Almeida, Margarete Teresa Gottardo (Springer Nature, 2025)
The scarce antifungal arsenal, changes in the susceptibility profile of fungal agents, and lack of adherence to treatment have contributed to the increase of cases of dermatomycoses. In this context, new antimicrobial substances have gained importance. Chalcones are precursors of the flavonoid family that have multiple biological activities, have high tolerability by humans, and easy synthesis. In this study, we evaluated the in vitro antifungal activity, alone and in combination with conventional antifungal drugs, of the VS02–4′ethyl chalcone-derived compound against dermatophytes and Candida spp. Susceptibility testing was carried out by broth microdilution. Experiments for determination of the target of the compound on the fungal cell, time-kill kinetics, and toxicity tests in Galleria mellonella model were also performed. Combinatory effects were evaluated by the checkerboard method. Results showed high activity of the compound VS02–4′ethyl against dermatophytes (MIC of 7.81–31.25 μg/ml). The compound targeted the cell membrane, and the time-kill test showed the compound continues to exert gradual activity after 5 days on dermatophytes, but no significant activity on Candida. Low toxicity was observed at 250 mg/kg. Excellent results were observed in the combinatory test, where VS02–4′ethyl showed synergistic interactions with itraconazole, fluconazole, terbinafine, and griseofulvin, against all isolates tested. Although further investigation is needed, these results revealed the great potential of chalcone-derived compounds against fungal infections for which treatments are long and laborious.
Keywords: Antifungal activity; Candida; Chalcones; Dermatomycoses; Dermatophytes; Synergistic interaction